Meshing Strategi untuk Memprediksi Hambatan Total pada Kapal Planing Hull - Fathuddiin, Abubakar; Samuel, Samuel (Jurnal Rekayasa Mesin, 2021)
A high-speed vessel has a range of Froude Number (Fr) > 1. A drag prediction method based on Fr > 1 has high complexity because it is influenced by trim and heave motions. Hence, a specific treatment is necessary to obtain accurate results. This study is using mesh density and mesh shapes to predict the total drag of a planing hull ship. The Computational Fluid Dynamic (CFD) results show good performance in predicting the drag, trim, and heave. Mesh density of 2300K shows the most stabilized result. The trimmed mesh type is more efficient to obtain accurate results because it has a smaller mesh size. The polyhedral mesh type is as good as trimmed mesh but is not as efficient as trimmed mesh and it has largely a time-consuming time.